2014
DOI: 10.1177/0022034514552490
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Monomer-free, Highly Crosslinked, Water-compatible Polymers

Abstract: Polymeric dental adhesives require the formation of densely crosslinked network structures to best ensure mechanical strength and durability in clinical service. Monomeric precursors to these materials typically consist of mixtures of hydrophilic and hydrophobic components that potentially undergo phase separation in the presence of low concentrations of water, which is detrimental to material performance and has motivated significant investigation into formulations that reduce this effect. We have investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Solution free radical polymerization produced particles with molecular weight in the 30–150 kDa range and radius <10 nm while avoiding macrogelation. The MH-α values are significantly reduced compared to typical values for a linear polymer and correspond well to previous reports on the GPC analysis of nanogels and hyperbranched polymers 25,31,32 .…”
Section: Resultssupporting
confidence: 90%
“…Solution free radical polymerization produced particles with molecular weight in the 30–150 kDa range and radius <10 nm while avoiding macrogelation. The MH-α values are significantly reduced compared to typical values for a linear polymer and correspond well to previous reports on the GPC analysis of nanogels and hyperbranched polymers 25,31,32 .…”
Section: Resultssupporting
confidence: 90%
“…We have previously demonstrated that nanogels can be efficiently functionalized with methacrylate groups via an alcohol-isocyanate click reaction and directly polymerized into crosslinked networks in the absence of small monomer 42,43 . Previous reports have further detailed the formation of covalently conjugated nanogel-based coatings on functionalized surfaces using a variety of click reactions including alkyne-azide, thiol-alkyne, and Michael addition reactions 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…Nanogels were synthesized as previously described (see supporting information and 42 ). Polyfluor 570 was included at 0.1 wt% to yield fluorescently tagged nanogels.…”
Section: Methodsmentioning
confidence: 99%
“…Nanomaterials are also efficient in reducing the friction of archwire. For instance, nanocoating materials made of Ni‐P and fullerene‐like nanoparticles of WS 2 or Co and fullerene‐like WS 2 nanoparticles (Dailing, Lewis, Barros, & Stansbury, 2014), nitrogen‐doped TiO 2 nanoparticles or Ag‐Zr nanocomposite coatings have shown both the friction reduction and corrosion resistance of the archwire. However, there are also limitations present, as the dissolve of nanoparticles from brackets may impair enamel esthetics, and thus affect the patient satisfaction after clinical treatment.…”
Section: Craniofacial Diseases Therapymentioning
confidence: 99%